Bridging literacy - Kosi, Liyema (Rhodes University, 2026)
Literacy is fundamental to educational success and social participation. However, global literacy levels remain unsatisfactory, particularly in countries like South Africa with low quality and unequal education. In post-apartheid South Africa, attempts to improve livelihoods have led to the development of various mechanisms and strategies aimed at addressing inequality gaps, particularly in the realm of education. One example is the mandate for higher education institutions to be socially responsive to the needs and wants of their local communities, based on the knowledge and resource exposure gained as they conduct their core functions of teaching and research. This study focuses on the community literacy programmes initiated by Rhodes University in Makhanda, evaluating their contribution to the development of literacy skills in foundation phase children at a non-fee primary school in the Joza community. Using a qualitative case study approach, data was collected through semi-structured interviews and analysed thematically. Social capital theory was then applied to explore the role of community-university partnerships in promoting literacy as part of community development. Findings reveal that such literacy programmes foster multi-level partnerships among stakeholders, enhance children's social-emotional development, and support the improvement of literacy practices in the school. The study highlights the importance of values such as mutual benefit, trust, and collective action in these partnerships formed within the literacy programmes.
the contribution of Rhodes Uuniversity literacy programmes in the literacy development of foundation phase children in a nonfee primary school in Joza, Makhanda
Keywords: Uncatalogued